2006
DOI: 10.1007/s10554-006-9134-3
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of late gadolinium enhancement combined with MRI and 67-Ga scintigraphy in the diagnosis of cardiac sarcoidosis and disease activity evaluation

Abstract: We report a case in which late gadolinium enhancement (LGE) and 67-Ga scintigraphy were useful for the diagnosis of cardiac sarcoidosis and for the evaluation of the disease activity. The patient was a 60-year-old woman who had been diagnosed as having eye sarcoidosis when she was 48. Two years previously her electrocardiogram had shown abnormalities but the coronary angiography had shown normal coronary arteries; however, an aneurysm was detected in the apical portion by left ventriculography. A II degree AV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…In the previous study including a relatively larger number of patients, LV systolic dysfunction were observed in 14% of 88 patients with systemic sarcoidosis, and wall motion abnormalities were generalized or localized to the base and mid level of the LV [4]. To our knowledge, there have been two case reports investigating the LV apical aneurysm in patients suffering from systemic sarcoidosis [5,6]. It would be clinically worthy to show a case with the LV apical aneurysm in cardiac sarcoidosis without obvious involvement of other organs.…”
Section: Discussionmentioning
confidence: 90%
“…In the previous study including a relatively larger number of patients, LV systolic dysfunction were observed in 14% of 88 patients with systemic sarcoidosis, and wall motion abnormalities were generalized or localized to the base and mid level of the LV [4]. To our knowledge, there have been two case reports investigating the LV apical aneurysm in patients suffering from systemic sarcoidosis [5,6]. It would be clinically worthy to show a case with the LV apical aneurysm in cardiac sarcoidosis without obvious involvement of other organs.…”
Section: Discussionmentioning
confidence: 90%
“…67-Gallium-citrate accumulates only in areas of active inflammation, T2-weighted MRI reveals edema with inflammation, and fasting 18F-FDG accumulation in PET indicates active inflammation. Positive findings in a 67-gallium-citrate scintigram and 18F-FDG PET indicate good response to steroid therapy [18,19]. Whether T2-weighted MRI can be used for evaluating response to steroid therapy requires further clinical study.…”
Section: Case Reportmentioning
confidence: 99%
“…Thus, Gallium-67 uptake is highly specific to inflammatory disease and a useful for detection of disease activity of cardiac sarcoidosis. Meanwhile, the main disadvantage is lack of sensitivity (20%, 36%) (Okayama et al, 1995;Kiuchi et al, 2007).…”
Section: Wwwintechopencommentioning
confidence: 99%